KARAKTERISTIK KIMIA DAN ORGANOLEPTIK KERUPUK JANTUNG PISANG KEPOK (Musa Paradisiaca balbisiana) DENGAN SUBSTITUSI TEPUNG MOCAF (MODIFIKASI CASSAVA) - Zulfa, Fitriyah; Mudzakiroh, Susi (Universitas Sebelas Maret (UNS), 2018)
Kerupuk is the most favourite snack in Indonesia. Kepok Banana flower (musa paradisiaca balbisiana) as the base componen of kerupuk bananan flower to up grade the economic margin. Substitution mocaf flavor from tapioca flavor to produce kerupuk without gluten. This research aim is to know chemical and organoleptic characteristic kerupuk bananan flower substituted with mocaf (modificated cassava). This product use banana kepok flower, mocaf with formula 90%:10%. Blend banana flower to smallest size, mix with mocaf and spice, steam 5 minute, and dry with cabinet drying 6 hour 50 0C to proseses it. Chemical characteristic show water level is 2%, protein is 0,37% and viber is 7 %. Organoleptic characteristic of banana flower with sensory analisis show mean score colour 5,2 (nearly like), score taste 6 (like), score tecsture 5,8 (like), score shape 4,7 (nearly like)and overall score are 5,7 (like). Suggested to make more innovation to produce banana flower mocaf crispy with more attractive in colour and shape.